2018
DOI: 10.1016/j.neuropsychologia.2018.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Agnosia for bird calls

Abstract: The cognitive organisation of nonverbal auditory knowledge remains poorly defined. Deficits of environmental sound as well as word and visual object knowledge are well-recognised in semantic dementia. However, it is unclear how auditory cognition breaks down in this disorder and how this relates to deficits in other knowledge modalities. We had the opportunity to study a patient with a typical syndrome of semantic dementia who had extensive premorbid knowledge of birds, allowing us to assess the impact of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…Furthermore, the functional connectivity maps showed that within the man-made category, there might be “key” connections for Artificial-versus-Natural relative to Musical-versus-Natural , even though the nodes remained the same for both comparisons. This could also explain cases of semantic impairments, where patients are impaired in a very specific category, while the remaining categories within the same domain are spared (McCarthy and Warrington, 2016; Muhammed et al, 2018). Therefore, it seems very probable that the perception of auditory objects relies on a large-scale distributed system, which follows distinct neuronal pathways, dissociated on the basis of the weight that each node has in the network.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the functional connectivity maps showed that within the man-made category, there might be “key” connections for Artificial-versus-Natural relative to Musical-versus-Natural , even though the nodes remained the same for both comparisons. This could also explain cases of semantic impairments, where patients are impaired in a very specific category, while the remaining categories within the same domain are spared (McCarthy and Warrington, 2016; Muhammed et al, 2018). Therefore, it seems very probable that the perception of auditory objects relies on a large-scale distributed system, which follows distinct neuronal pathways, dissociated on the basis of the weight that each node has in the network.…”
Section: Discussionmentioning
confidence: 99%
“…First, Omar et al (2010) documented a professional trumpeter with SD, who retained the ability to recognise musical notation but showed an impairment in auditory music knowledge. Second, Muhammed et al (2018) reported on BA, a case of SD who had premorbid expertise in the domain of bird knowledge. Muhammed et al (2018) tested BA's knowledge of avian characteristics (size, behaviour and habitat) in the verbal, visual and auditory modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Second, Muhammed et al (2018) reported on BA, a case of SD who had premorbid expertise in the domain of bird knowledge. Muhammed et al (2018) tested BA's knowledge of avian characteristics (size, behaviour and habitat) in the verbal, visual and auditory modalities. Relative to the performance of three healthy bird experts of a similar age, BA had an impairment in verbal and auditory bird knowledge but relatively preserved knowledge of avian visual attributes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations